Scaling the complexity of a Philippine consumer-finance contract through reader-based and text-based measures - Lintao, Rachelle Ballesteros (Philippine Journal of Linguistics, 2014)
This study sought to determine how a group of target users’ evaluation of a Philippine consumer-finance contract compares with the measured complexity of the document. Using a text computational tool, results of the analysis through the document’s computed values and substantiated by other readability computational tools employed reveal that the existing document can be understood by those within the range of the 11-CCR grade band. The complication arises since these measures do not correspond with the level of the participants, regarded to be way below the 11-CCR grade band, deemed to be only 8-10 US grade level. Conversely, the document is too difficult to be understood by the participants. The low comprehensibility of the material as scaled by the participants results from their deficient understanding of the document brought about by their lack of capability to grasp such an obfuscated or complicated document. This study has established that the use of a cognitively inspired text computational tool can be effective in validating the complexity of a reading material. Going beyond the difficulty of words and sentence length which traditional readability tools dwell on, cognitively-enthused readability tools like the coh-metrix allow for examining the deeper dimensions of the text like referential cohesion, syntactic pattern and text easability. ​